Trustworthy Computing and Services c - Yuan, Yuyu.; Wu, Xu.; Lu, Yueming; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the International Standard Conference on Trustworthy Distributed Computing and Services, ISCTCS 2012, held in Beijing, China, in May/June 2012. The 92 revised full papers presented were carefully reviewed and selected from 278 papers. The topics covered are architecture for trusted computing systems, trusted computing platform, trusted systems build, network and protocol security, mobile network security, network survivability and other critical theories and standard systems, credible assessment, credible measurement and metrics, trusted systems, trusted networks, trusted mobile network, trusted routing, trusted software, trusted operating systems, trusted storage, fault-tolerant computing and other key technologies, trusted e-commerce and e-government, trusted logistics, trusted internet of things, trusted cloud and other trusted services and applications.
Architecture for trusted computing systems -- Trusted computing platform -- Trusted systems build -- Network and protocol security -- Mobile network security -- Network survivability and other critical theories and standard systems -- Credible assessment, credible measurement and metrics -- Trusted systems -- Trusted networks -- Trusted mobile network -- Trusted routing -- Trusted software -- Trusted operating systems -- Trusted storage -- Fault-tolerant computing and other key technologies -- Trusted e-commerce and e-government -- Trusted logistics -- Trusted internet of things -- Trusted cloud and other trusted services and applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Operating systems (Computers).; Data protection; Data encryption (Computer science).; Database management; Computer Science; Systems and Data Security; Computer Communication Networks; Software Engineering; Operating Systems; Data Encryption; Database Management